Active labor market policies in the framework of Just Transition Programs: the case of Italy, Spain, and Germany - Valeria Cirillo; Marialuisa Divella; Eustachio Ferrulli; Lidia Greco (Austrian Foundation for Development Research (ÖFSE), 2024)
Within the context of the green industrial policies debate, this paper seeks to examine the progress of policy implementation regarding the upskilling and reskilling of workers under the European Just Transition Fund (JTF) 2021-27. Specifically, it focuses on distinct regions in three countries: Italy, Spain, and Germany. Through a combination of desk research and qualitative analysis via interviews with key informants, the research aims at assessing the advancement of training and retraining interventions for workers in those regions and identifying any implementation deficiencies and critical challenges encountered by these initiatives. The paper thus aims to contribute to the ongoing debate on green industrial policies and their implications for just transition and workforce development. Although it is too early for a comprehensive assessment due to limited actions in this field based on JTF implementation so far, some relevant policy implications can be drawn. These refer in particular to the need of better integrating the active labor market policy interventions under examination with a more comprehensive regional development strategy, while taking account of regional specificities and actual workers' needs in such specific contexts.
Keywords: 330; Just transition; active labor market policies; workers' upskilling and reskilling; industrial policy